„Witkacy rzucił się jak szczerbaty na suchary” Witkiewicz w czasie pierwszej wojny światowej - Okołowicz, Stefan (Przestrzenie Teorii, 2010)
Okołowicz Stefan, „Witkacy rzucił się jak szczerbaty na suchary”. Witkiewicz w czasie pierwszej wojny światowej [“Witkacy darted like a gap-toothed person onto rusk”. Witkiewicz during the First World War]. „Przestrzenie Teorii” 14. Poznań 2010, Adam Mickiewicz University Press, pp. 235-249. ISBN 978-83-232-2210-1. ISSN 1644-6763. This text is a polemic with an article by Maria A. Potocka “Ja” jako materiał twórczy [“I”as a material for creation]. When considering the problem of the presence of Witkacy in the Tsarist army, the author comes to a conclusion that Witkiewicz went there where he did not intend to go, misled by inaccurate information. The choice of the Russian opportunity based on incomplete or untrue information and unsuccessful coincidences – according to the author – should be considered in the categories of Witkacy’s personal tragedy no matter what significance this fact gained later